PENERAPAN GAME BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN NUMERASI SISWA SEKOLAH DASAR - Asri, Putri Fauziahtul; Jufri, Windry Novalia; Zuwida, Nidal (Teknik Sipil Universitas Negeri Padang, 2025)
Numeracy skills are essential for developing critical thinking and problem-solving abilities. However, the 2023 National Assessment results show that students at SDN 20 Sinapa Piliang, Solok City, achieved only moderate numeracy scores (58.75%), below the national average. To address this, lecturers and students from Universitas Negeri Padang conducted a community service program in August 2025, training elementary school teachers to apply Game-Based Learning (GBL). The program included socialization of GBL concepts, training to create numeracy game media, classroom simulations, and evaluation. Teachers were introduced to number-operation cards, traditional games, and the Kahoot digital platform as interactive teaching tools. The program improved teachers’ understanding of GBL principles and their ability to adapt games in their teaching. Teachers also showed strong enthusiasm to apply the methods, suggesting digital game development and implementing them in class. This program is expected to support the improvement of students’ numeracy skills through more engaging and innovative learning practices.